PERANCANGAN IKAT PINGGANG ELEKTRONIK UNTUK TUNANETRA MENGGUNAKAN MIKROKONTROLLER DAN GLOBAL POSITIONING SYSTEM (GPS) PADA SMARTPHONE ANDROID - Derisma, Derisma; Firdaus, Firdaus; Yusya, Rio Putra (Jurnal Teknik Elektro, 2016)
Discoveries in a variety of sensor technologies in such HCSR bluetooth module HC 04 and 05 and global positioning system (GPS) on the Android smartphone, but the use is not maximized. The author tries to apply HCSR sensor 04 as an obstacle detection at blindman when walking and HC module 05 serves as a liaison tool with android smartphone that also serves as a conduit of location information using GPS blind in sound output. Measuring distance manually using the results 83.33% rule comparable to that read by the sensor HCSR 04 bluetooth connection using bluetooth module HC 05 has a maximum distance of 18 meters. The use of GPS is more effectively used in sunny weather conditions with averaged data retrieval 2.3 second and in a state of rest with a time of 2.6 second